High-intensity interval training (HIIT) and inpatient energy management education (IEME) in persons with multiple sclerosis (pwMS): Process description of a randomized controlled trial with six-month follow-up. - Patt, Nadine; Nigg, Claudio R.; Bansi, Jens (Current Issues in Sport Science (CISS), 2023)
Introduction Fatigue is one of the most frequent symptoms in pwMS, affecting their health-related quality of life (HRQoL; Amato et al., 2001). A multimodal rehabilitation approach is recommended for a successful management of symptoms but strong evidence to date is available only for unimodal interventions (exercise or energy management programs; Khan & Amatya, 2017). Objective This presentation will focus on the process description of conducting a randomized controlled trial to evaluate the effect of the combination of HIIT and IEME in pwMS. Methods Participants were recruited at the rehabilitation centre in Valens. Experimental group (EG): during the three-week rehabilitation stay, the participants performed IEME twice and HIIT three times per week. IEME: group-based intervention, lasting for 6.5h over three weeks. HIIT: five 1.5-min high-intensive exercise bouts on a cycle ergometer at 95–100% of peak heart rate (HRpeak). Control group (CG; local usual care): participants performed progressive muscle relaxation (PMR) twice and moderate continuous training (MCT) three times per week during the three-week rehabilitation stay. PMR: six 1-h relaxation group sessions over three weeks. MCT: 24-min continuous cycling at 65% of HRpeak. Primary endpoint: HRQoL (Physical and Mental Component Summaries of the Medical Outcome Study 36-item Short Form Health Survey; SF-36), measured at entry to the clinic (T0), three weeks after T0 (T1) and at four (T2) and six (T3) months after T0. Process results In February 2021, a study protocol was published (Patt et al., 2021). Between July 2020 and October 2021, 182 pwMS with an Expanded Disability Status Scale (EDSS) score ≤ 6.5 entered the clinic, of whom 106 were randomized into one of the two intervention groups (EG: n = 53, CG: n = 53). The last follow-up was completed in May 2022. There was one missing questionnaire at T1 (EG). At T2 and T3, six (EG: n = 3, CG: n = 3) and seven (EG: n = 3, CG: n = 4) participants did not return the questionnaires, respectively. The average training intensity in the HIIT group was 102.64% HRpeak (n = 52, one dropout) and in the MCT group was 79.48% HRpeak (n = 53). Three (5.7%) participants were non-compliant to IEME (reasons: no need [n = 3]) and two (3.8%) participants dropped out of PMR (reasons: feeling uncomfortable in group-setting [n = 1], not relaxing [n = 1]). Discussion The process results reflect successful recruitment and high response rates. However, adherence was afflicted by training at higher intensities than prescribed, especially in the CG. References Amato, M. P., Ponziani, G., Rossi, F., Liedl, C. L., Stefanile, C., & Rossi, L. (2001). Quality of life in multiple sclerosis: The impact of depression, fatigue and disability. Multiple Sclerosis Journal, 7(5), 340-344. https://doi.org/10.1177/135245850100700511 Khan, F., & Amatya, B. (2017). Rehabilitation in multiple sclerosis: A systematic review of systematic reviews. Archives of Physical Medicine and Rehabiltation, 98(2), 353-367. https://doi.org/10.1016/j.apmr.2016.04.016 Patt, N., Kool, J., Hersche, R., Oberste, M., Walzik, D., Joisten, N., Caminada, D., Ferrara, F., Gonzenbach, R., Nigg, C. R., Kamm, C. P., Zimmer, P., & Bansi, J. (2021). High-intensity interval training and energy management education, compared with moderate continuous training and progressive muscle relaxation, for improving health-related quality of life in persons with multiple sclerosis: Study protocol of a randomized controlled superiority trial with six months’ follow-up. BMC Neurology, 21, Artcile 65. https://doi.org/10.1186/s12883-021-02084-0